Mitigation of problems by Project Managers during industrial revolution 4.0 in the Klang Valley, Malaysia - Mohd Saad, Mohd Haris (2022)
Construction projects in Malaysia especially in Klang Valley are often challenged with issues such as delay, safety and quality because the issues kept recurring. These are common problems in this industry which are caused either by human behaviour, nature or working surrounding environment which influences the situation. Lack of communication contributes most on the emerging issues. Strong communication behaviour is important to mitigate the arising issues in construction projects. The solutions had been suggested by the previous studies but the solution haven’t solved. The existence of hierarchy in the workflow sometimes reduces the speed of the construction work progress. The objectives are to identify the types of issues that are commonly observed at construction site projects, to investigate the methods to solve the issues observed at construction site projects and to determine the mitigation methods to overcome the issues using relevant technologies of I.R 4.0 that match the type of problems to improve the working climate. The implementation of I.R 4.0 in construction projects seems effective to mitigate issues in construction projects as compared to traditional methods. Most of the interviewees agree that the implementation of I.R 4.0 as seen in the use of either gadgets, software or tools in their working environment contribute to the efficiency of their work and smoothed the work process among government sectors, government link companies, consultants and contractors. The efficiency of the communication between the personnel involved increases the success rate of the projects in terms of completion time. This study applies a mixed-method approach which consists of survey and semi-structured interviews. This is to ensure a rigorous study conduct where triangulation of data is performed. 150 online and printed questionnaires were distributed to selected respondents. Among these, the printed copies of the questionnaire were distributed to government staffs, consultants and contractors. Out of the 150 questionnaires distributed, only 36 were returned and analysed statistically using SPSS. The major focus of the data collection process was the qualitative semi-structured interviews in which eight participants were interviewed; whereas the other seven participants could not be interviewed for personal reasons. The eight interviewees are two government staff, one consultant and five contractors. The depth of information is obtained from the qualitative data analysis. The interview sessions were conducted online due to the restrictions enforced because of Covid-19 pandemic. Nvivo 1.6 was used for qualitative data analysis after the transcription process was done. The results from the analysis show that interviewees and respondents employing the I.R 4.0 tools in their projects and will lead the road of successful in construction projects towards the future, and ultimately, the use of these I.R 4.0 tools would benefit the construction project site personnel to their working surrounding climate.